A study protocol for a non-randomised evaluation of a growth-based career construction psychosocial intervention for higher education students - Chim, Kathleen; Lai, JoJo T. C. (Frontiers in Education, 2024)
Background Despite promising emerging evidence on the protective properties and interrelationships of posttraumatic growth, career adaptability and psychological flexibility, no studies have reported interventions that promote these positive personal resources among higher education students. Nurturing these positive personal resources in future interventions is recommended to holistically address students’ developmental, academic and career-related challenges associated with major transitions. This paper describes (a) the rationale for and development of a tailored growth-based career construction psychosocial intervention, ‘Sailing through Life and My Career Path’ (SLCP) for higher education students; and (b) a mixed-method non-randomised pre-post study to evaluate the effectiveness of the proposed psychosocial intervention in achieving positive participant outcomes. Methods and analysis Over a 12-week period, higher education students will be recruited to take part in group and independent learning activities that are tailored to nurture positive personal resources to overcome challenges related to developmental, academic and career-related transitions. Quantitative data will be collected before and after the intervention and will be analysed using SPSS v26. Follow-up semi-structured interviews with participants (students), interventionists (group facilitators), and administrators will be conducted to explore perceptions of the intervention, to understand its process of change, and to determine its feasibility and acceptability in the higher education setting. All interviews will be transcribed and analysed using thematic analysis. Discussion By filling in a gap in existing intervention research and practice, the proposed study serves to generate new knowledge and insights by evaluating the effectiveness of a tailored psychosocial intervention that responds to the complex needs associated with major life transitions of higher education students.